The Correlation of Catering Incentives to Stock Return - A Test of Catering Theory of Dividend - ARIANA RESTU HANDARY; NIKI LUKVIARMAN; RAHMAT FEBRIANTO (The Indonesian Journal of Accounting Research, 2013)
This research investigates whether dividend catering theory can provide the answer to explain phenomenon of dividend policy in Indonesia. The theory argues that the decision to pay dividends is driven by investors demand. Managers pay dividend when investors put a higher price on the shares of dividend payers and not paying when investors prefer non-dividend payers. Dividend premium is used as the proxy for the investor sentiment for dividend. The sample of this research is 337 non-financial firms listed within the Jakarta Stock Exchange, which is composed of 363 dividend announcements during the period 1999-2003. The correlation between catering incentives, measured by dividend premium, and the stock return shows a negative association between dividend premium and the stock return. Such a negative relationship might be caused by the relative growth opportunity of the firms showed by the decreasing number of dividend payers during period of observation.